NRAMP gene family in Kandelia obovata: genome-wide identification, expression analysis, and response to five different copper stress conditions - Hussain, Quaid; Ye, Ting; Shang, Chenjing; Li, Sihui; Khan, Asadullah; Nkoh, Jackson Nkoh; Mustafa, Abd El-Zaher M. A.; Elshikh, Mohamed S. (Frontiers in Plant Science, 2024)
Natural resistance-associated macrophage proteins (NRAMPs) are a class of metal transporters found in plants that exhibit diverse functions across different species. Transporter proteins facilitate the absorption, distribution, and sequestration of metallic elements within various plant tissues. Despite the extensive identification of NRAMP family genes in various species, a full analysis of these genes in tree species is still necessary. Genome-wide identification and bioinformatics analysis were performed to understand the roles of NRAMP genes in copper (CuCl2) stress in Kandelia obovata (Ko). In Arachis hypogaea L., Populus trichocarpa, Vitis vinifera, Phaseolus vulgaris L., Camellia sinensis, Spirodela polyrhiza, Glycine max L. and Solanum lycopersicum, a genome-wide study of the NRAMP gene family was performed earlier. The domain and 3D structural variation, phylogenetic tree, chromosomal distributions, gene structure, motif analysis, subcellular localization, cis-regulatory elements, synteny and duplication analysis, and expression profiles in leaves and CuCl2 were all investigated in this research. In order to comprehend the notable functions of the NRAMP gene family in Kandelia obovata, a comprehensive investigation was conducted at the genomic level. This study successfully found five NRAMP genes, encompassing one gene pair resulting from whole-genome duplication and a gene that had undergone segmental duplication. The examination of chromosomal position revealed an unequal distribution of the KoNRAMP genes across chromosomes 1, 2, 5, 7, and 18. The KoNRAMPs can be classified into three subgroups (I, II, and SLC) based on phylogeny and synteny analyses, similar to Solanum lycopersicum. Examining cis-regulatory elements in the promoters revealed five hormone-correlated responsive elements and four stress-related responsive elements. The genomic architecture and properties of 10 highly conserved motifs are similar among members of the NRAMP gene family. The conducted investigations demonstrated that the expression levels of all five genes exhibited alterations in response to different levels of CuCl2 stress. The results of this study offer crucial insights into the roles of KoNRAMPs in the response of Kandelia obovata to CuCl2 stress.